Problematic and adaptive eating in people with obesity after a DBT-based skills training intervention: 3- and 8-month follow-up and mediation analysis - Souza,Lucas André Schuster de (2019)
Abstract Background: Dialectical behavior therapy conceptualizes problematic behaviors as attempts to regulate emotions that occur when the individual lacks effective skills with which to manage his or her emotions and cope with distress. Problematic eating behaviors, e.g., binge and emotional eating, may serve to alleviate aversive emotional states, being highly associated with overweight and obesity. Dialectical behavior therapy skills training has been proven effective in reducing binge eating in several clinical studies. However, few studies reveal the effects of DBT on adaptive eating behaviors or the stability of outcomes. Objectives: This study aimed to test the effect of a brief DBT-based skills training intervention, and the stability of outcomes at 3- and 8-month follow-ups. Methods: Self-report measures of binge eating, emotional eating, intuitive eating, and mindful eating were taken on 5 timepoints before and after a 10-session DBT skills training intervention (2 baseline measures, 1 post-test, and 2 follow-ups). Data were analyzed using a mixed-model intention-to-treat approach and mediation analysis was conducted with path analysis. Results: After the intervention, intuitive eating and mindful eating scores were significantly higher than before the intervention, while emotional eating and binge eating scores were lower. The results remained stable during the follow-up period, with minor fluctuations and small trends towards returning to baseline values for binge eating and emotional eating. Mindful eating partially mediated the improvements in all outcomes. Limitations: Given that results are entirely based on self-report measures and that some instruments showed poor reliability, in addition to the high attrition rates, the results should be interpreted as preliminary. Conclusions: The results provide evidence that a brief DBT intervention is effective not only in reducing problematic eating but also in increasing adaptive eating, achieving reasonably stable results. Also, the mediation analysis results support the hypothesis that mindful eating partially explains the effects of the intervention on binge and emotional eating. Future research should address the limitations of this study by investigating a more diverse sample, triangulating different measurement strategies, and including other putative mediators.